Development of PBL-Based Science Worksheets on Natural Disaster Mitigation Materials to Increase Middle School Students’ Natural Disaster Preparedness Attitudes - Pratama, Danang Habib; Hamidi, Azrul; Nurohman, Sabar (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2023)
This study aims to determine the practicality and readability of PBL-based science worksheets on natural disaster mitigation material to improve the attitude of preparedness for natural disasters in junior high school students. This development research adheres to the 4D development model which includes define, design, develop, and disseminate. This research only reached the develop stage due to research limitations. Based on the results of the study, it was shown that the science teacher’s response to the product obtained an average score of 3.36 with very good criteria, while the results of students’ responses to the developed LKPD product obtained an average score of 3.50 with strongly agree criteria. Furthermore, based on the results of product trials and filling out the attitude questionnaire for natural disaster preparedness, students before and after the activity and analyzed using n-gain obtained an average score of 1.23 in the high category. Based on the results of teacher and student responses, that valid product is used to improve junior high school students’ natural disaster preparedness attitudes.